Extremism in the police: a reference handbook - Lewandowski, Carla (Contemporary world issues, 2024)
"A comprehensive and even-handed summary of historical and contemporary perspectives on ideological extremism in law enforcement and its wider impacts on American society"-- Provided by publisher